Practices and challenges on economic empowerment of rural women in Halaba Special Woreda, SNNPR, Ethiopia - Hassen, B. (Indira Gandhi National Open University, 2011)
Women’s economic empowerment helps to insure gender equality and the well being of nations. When women become economically empowered and get their own source of income definitely they insure the basic needs of the family (Raesser, Blumberg 2006). The purpose of the study was to assess the practice and challenges on economic empowerment of rural women in Halaba Special Woreda in S.N.N.P.R of Ethiopia. Standing from this objective, the study attempted to answer the basic questions of what are the factors that contributed to women’s economic dependency, the effort exerted by the government to empower women’s economically and the challenges in the implementation process. The study was conducted using descriptive study design. The total sample size of the study was 353 respondents from 6 kebeles of Halaba Special Woreda. After the representative sample size is determined using Cochran’s (1997) formula, simple random sampling and purposive sampling techniques were used to select the sample from the source population. The data collection was done through questionnaire for quantitative survey and interview for qualitative survey. After the data has been collected it’s analyzed supporting with tables and figures. The Challenges and practices on economic empowerment of rural women in Halaba Special Woreda were illiteracy rate among women’s, cultural influence, limited participation in decision making process, having limited access of land and other properties, inadequacy of organization that focus on women’s economic empowerment to deliver the needed services for credit availability were the main findings of the study . Even though, the government declared equality of property right for women, most of them in the study area were not entitled to land.